14. DELAYED MRI RESPONSE TO LITT IN PATIENTS UNDERGOING IMMUNOTHERAPY. (4th August 2020) - Hong, Christopher; Chiang, Veronica
Abstract: Laser interstitial thermal therapy (LITT) is an effective treatment for regrowing lesions after previous radiosurgery to brain metastases, typically resulting in decreased perilesional edema within weeks followed by delayed reduction in lesion size. We have anecdotally observed that patients on immunotherapy (IT) at time of LITT may exhibit a delayed edema resolution response to laser ablation. Post-operative imaging for cases of LITT, performed by the senior author from June 2012-July 2019, for regrowing lesions after prior radiosurgery for brain metastases were retrospectively reviewed. The IT group was defined as any patient receiving IT treatment within 3 months of LITT. Post-operative MRIs obtained at serial time points after surgery (2 weeks, 6 weeks, 3 months, 6 months, and 12 months) were reviewed for treatment response to LITT, defined as change in surrounding edema on T2 FLAIR and change of lesion size on T1-weighted post-contrast images. Out of 60 ablated lesions, 22 were in the IT and 38 were in the non-IT groups. There were no differences in distribution of original cancer pathology (IT: 9 melanoma, 8 lung, 5 other, non-IT: 6 melanoma, 20 lung, 12 other; p>0.05). Time to lesion size response on T1-weighted post-contrast MRI neared but did not reach statistical significance between the IT and non-IT groups: median 3.0 versus 2.25 months (HR 1.5, 0.8–2.5, 95% CI, p=0.08), respectively. However, time to reduction of perilesional edema on T2-weighted MRI was significantly longer in the IT group, compared to the non-IT group: median 2.25 versus 1.5 months (HR 1.5, 0.9–2.5, 95% CI, p=0.04), respectively. These data suggest that IT around the time of LITT may lead to delayed edema reduction on MRI after LITT. We hypothesize IT may enhance normal immune-mediated mechanisms thus increasing perilesional inflammation after LITT. Further studies are needed to corroborate our observations and explore the underlying pathophysiology.